Blue skies in the making: Air quality action plans and urban imaginaries in London, Hong Kong, and San Francisco. (February 2019) - Gross, Patrick Léon; Buchanan, Nicholas; Sané, Sabine
Abstract: Air quality action plans (AQAPs) are emerging as a promising governance tool that cities employ in pursuit of clean air transitions. Representing a city's blueprint for achieving a particular air quality objective, these plans both describe a particular vision of what a blue sky urban future should look like and provide the mechanism by which the city aims to achieve this vision. As such, AQAPs constitute an important shift from a highly fragmented and instrumental environmental policy towards an integrated strategy guided by a long-term vision. This article unpacks the visionary fabric undergirding AQAPs as well as their media representations by means of content analysis. Using three concrete case studies–London, Hong Kong, and San Francisco–the analysis is guided by Jasanoff and Kim's concept of sociotechnical imaginaries. The concept states that societies hold collective visions about desirable futures that are institutionally stabilized and publicly performed, ultimately coming to shape policy agendas and developmental trajectories. The application of this concept to AQAPs contributes in two ways. First, it addresses questions about the similarity and fragmentation of environmental policy in the global arena. By providing evidence for the similarity of imaginary structures between cities, it supports observations of a striking uniformity in governance patterns of environmental policy. Second, the article discusses what sociotechnical implications AQAPs may have for the city. It does so by elaborating on five storylines driving imaginaries of urban futures and pointing out the possibilities and limitations they delimit: 1. the government-up-front, 2. the new economy of clean air, 3. the technological fix, 4. remaking the 'good' urban citizen, and 5. the science-policy interplay.